European Trade and Foreign Direct Investment U-Shaping Industrial Output in Central and Eastern Europe : Theory and Evidence - Walsh, Patrick (IMF Working Papers; Working Paper ;, 1998)
We examine industrial output in Bulgaria, Hungary, Poland, and Romania during 1989-95 in terms of pretransitional product trade orientation. The growth of EU-oriented output within sectors of industry, ex-post trade, and market liberalization, is modeled as foreign direct investment induced Schumpeterian (vertical) waves of product innovation. The growth of non-EU-oriented output within sectors is modeled as unobservable deterministic heterogeneity. The results indicate that the gap observed in industrial output performance when comparing Eastern European to former Soviet countries is mainly explained by the inherited presence of EU-oriented production and its unconstrained growth over the transition period.